The education of nurses working in care homes for older people: An Appreciative Inquiry. (3rd February 2019) - Jack, Kirsten; Tetley, Josie; Chambers, Alison
Abstract: Aim: To explore the education and developmental needs of care home nursing staff. Background: With an increasing ageing population, the need for high‐quality care provision is set to rise and will require nursing staff with the desired knowledge, skills and values. However, multiple concerns have been identified when considering the development of nurses working in care homes. Moreover, challenges in the care home sector have also contributed to a situation where some nurses view care home work as being of low status and choose this work to fit around other commitments, rather than viewing it as a viable career pathway. Method: A qualitative approach based on the principles of Appreciative Inquiry. Fifteen participants working in five care homes with nursing, based in England (UK), took part in this study. Data were collected during 2016–2017 and involved managerial, qualified and unqualified staff. Results: Data analysis revealed three distinct themes: an effective learning environment; the care home as a nursing student placement; and the need for financial investment. These themes were found to have the most influence on the development and education of care home nursing staff. Conclusion: This research provides important insights into the care home as an educational environment, not only for nursing students but also for those employees already working in such settings. Exploration of the ways in which higher education organisations and care home teams could collaborate more closely could be mutually beneficial to the quality of care and to raising the profile of care home work. Implications for practice: Care homes can provide a rich learning environment for both staff and nursing students. Collaboration and appreciative ways of working enhance opportunities for developing practice and care.